Perancangan Ulang Upt Perpustakaan Universitas Negeri Malang Pendekatan Ekologi Arsitektur - Putri Zeylabiba, Napbella; Hambali Wilman Abdulhadi, Reza; Septony Siregar, Fernando (eProceedings of Art & Design, 2024)
Higher education libraries support learning, research, and community service in accordance with Government regulation Number 30 of 1990. State University of Malang (UM) has a UPT Library as a reference center for scientific information for 120 study programs. In addition, the UM UPT Library is also open to general public so that the UM UPT Library continues to develop innovations, including by introducing the Blended Eco Library concept to support UM vision as a superior university and UM achievement in the UI Green Metric World University Rankings. However, there are still problem related to design development that applies the Blended Eco-Library concept. Apart from problems encountered from the survei results, namely in the organization and cieculation of space, visual concepts, and general requirements. Therefore, redesigning the UM Library is must. The aim is to create a library that is more relevant, efficient, and effective in supporting education, research, and development in the field of education so that it can fulfill the vision of itself. The methods used for the redesign of the State University of Malang (UM) Library include data collection through interviews, questionnaires, obsevations, field studies, literature studies, comparative studies, and precedent studies. The final result of this design is a design concept based on the problems that have been identified, and leads to design output in the form of design animations and mockups. Keywords: library, university, blended, eco-library, Malang